WAYANG SEBAGAI MEDIA PENYIARAN ISLAM: STUDI ATAS STRATEGI DAKWAH WALISONGO DI JAWA - Muhammad Sungaidi (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2016)
Shadow puppets is portrait of life that contain sanepa (satire), piwulang (teachings), and pituduh (advices). Puppets contains habits, behavior, ethics of human life and natural conditions. The story of puppet reflects the signs of human life. Between the one role and the other are different. the plot in shadow puppets illustrates the circle of human life, from birth, adulthood and death. In this process humans always strive for a balance between human Nature and God Almighty. This puppets was then used by the Javanese Nine Saints (Wali Songo) to Islamizing Java.